Systematic Review Children's Immunity Response to Covid-19 Infection - Yuly Peristiowati; Semi Semi (Jurnal Keperawatan, 2022)
Immunity is resistance from infection and the immune response is the coordination of cells in the body and other molecules against infection. Corona Virus is a positive chain Ribonucleic acid (RNA) virus whose transmission occurs more often from infected closest relatives with the main route through inhalation. direct respiratory droplets from coughing and sneezing. This systematic review aims to identify the immune response of children infected with Covid-19. Search articles using 4 databases, namely Scopus, ProQuest, Pubmed, and Science Direct using keywords and Boolean operators. Strategy to find articles using PICO. The results obtained 14 articles, assessment using PRISMA checklist.The results of the review show that SARS-CoV-2 infection in children triggers non-specific and specific immune responses. The non-specific immune response begins with an increase in white blood cells and triggers a specific immune response, namely T and B cells that will produce antibodies. There are increased levels of CRP, IL-6, IL-10, IFN-g,TNF-a and IP-10 which can be an independent predictor of disease severity. Excessive levels of mediators can causes a cytokine storm that damage the human body and increased D-dimer in severe cases. The specific immune response will mediate the formation of antibodies. B cells are assisted by T cells to differentiate into plasma cells, which then produce specific antibodies for viral antigens, in the form of IgM which is detected early and is then replaced by IgG. To improve the performance of the immune system, there needs to be an increase in nutrition, adequate rest, support and family motivation.